Using physiological MRI to estimate dynamic cerebral autoregulation metrics: functional MRI feasibility study - Hawezi, Negar (2015)
Cerebral autoregulation is the homeostatic mechanism that maintains sufficient cerebral circulation despite changes in the perfusion pressure. Dynamic CA refers to the changes that occur in CBF within the first few seconds after an acute MAP change. Assessment of the CA impairment plays important role in the prognosis of many cerebrovascular diseases such as stroke, sub-arachnoid haemorrhage, as well as traumatic brain injury and neurodegenerative disorders.